Saudi Arabia : 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
Saudi Arabia is the world's largest oil exporter and has employed its spare capacity to help stabilize the global oil market, providing important support to the global economy. The associated increase in oil revenues has resulted in sharply higher fiscal and current account surpluses and provided room to accelerate initiatives to address pressing social issues, including a shortage of affordable housing and unemployment. Spillovers from higher growth and fiscal spending, together with increased financial assistance, have positively impacted the region.